PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SOSIALISASI SEBAGAI VARIABEL MODERASI - Ardana Ayu Andiaty; Umaimah Umaimah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to examine the effect of modernization of the tax administration system and tax sanctions on taxpayer compliance with socialization as a moderating variable. This research is quantitative research using primary data sources obtained from distributing questionnaires. The determination of respondents in this research was carried out using a purposive sampling method with the number of respondents being 70 Individual Taxpayers and Entrepreneurs. The analytical method of this research uses descriptive analysis and hypothesis testing with the help of SmartPLS 4 software. The results of the research show that: (1) modernization of the tax administration system has no effect on taxpayer compliance, (2) tax sanctions have an effect on taxpayer compliance, (3) socialization is unable to moderate the influence of the relationship between modernization of the tax administration system and taxpayer compliance, (4) socialization is unable to moderate the influence of the relationship between tax sanctions and taxpayer compliance.